Public relations in the educational system - Zlatanović-Marković Valentina; Nikolić Biljana; Stakić Mirjana; Mitić Milovan (Megatrend Revija, 2022)
The aim of this paper is to determine the effects of the implementation of the program "School and the public" on the organization of the school system in the period of program implementation from 2009-2014. and the level of communication between the education system and the public. Methods: 694 respondents fulfilled the questionnaire for the training participants used in actual research, and prepared by the Institute for the Advancement of Education and Upbringing, intended exclusively for the Center for Professional Development of Employees. The collected data were processed by descriptive statistics in Microsoft Excel and the results obtained are presented in tables and graphs. Results: The fact that the large percentage of participants (more than 90%) spoke positively about the program speaks in favor of the claim that employees in education are aware of the need for personal training and engagement in communication processes between the educational institution and the public. CONCLUSION: Participants' answers clearly indicated the obvious improvement of communication between the educational institution and the public through the affirmation of the work of the institution itself, as well as the establishment of a positive image and solving important issues and problems in the functioning and work of the institution.